Ion exchange membrane as well as preparation method and application thereof
By deprotonating the first polymer film and tensile modification, an ion exchange membrane with excellent mechanical properties and good conductivity was prepared, which solved the problem of mechanical properties of the ion exchange membrane after absorbing alkali liquid in the prior art, and simplified the preparation process.
Patent Information
- Application Number
- CN202411286800.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The mechanical properties of existing ion exchange membranes decrease after absorbing alkali liquid, and the improvement methods are complex and difficult to apply on a large scale.
By deprotonating the first polymer film and tensile modification, an ion exchange membrane with excellent mechanical properties and good conductivity was prepared. This method does not require designing new monomers or performing complex reactions such as crosslinking and organic inorganic complexing.
The mechanical properties of the ion exchange membrane are improved, such as strengthening strength and modulus, while maintaining a high conductivity, solving the problem of mechanical properties and simplifying the preparation process.
Smart Images

Figure CN119552400A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of ion exchange, and in particular to an ion exchange membrane and a preparation method and application thereof. Background Art
[0002] With the development and application of renewable energy such as wind energy and solar energy, the output of green electricity is increasing year by year. In order to safely absorb and store the rapidly growing green electricity, the electrolytic hydrogen production technology of water electrolysis in electrolyzers has attracted more and more attention.
[0003] At present, the electrolyzer based on the proton exchange membrane of perfluorosulfonic acid membrane has the characteristics of high efficiency and pure gas production. However, since the electrode material inevitably uses precious metal catalysts such as platinum, iridium, and ruthenium, it is difficult to develop the electrolyzer of proton exchange membrane on a large scale. Based on this, the traditional alkaline electrolyzer that can use non-precious metal catalysts is widely used due to its low cost and high durability.
[0004] In recent years, the rapidly developing anion exchange membrane electrolyzer combines the advantages of proton exchange membrane and alkaline electrolyzer, making it expected to become the next generation of low-cost, high-efficiency core technology for hydrogen production by electrolysis of water. However, the disadvantage of the instability of quaternary ammonium salt functional groups makes it difficult to operate for a long time, and it is still a long way from the requirements of industrialization. Another feasible idea is to introduce ion solvent membranes into alkaline electrolyzers. This semi-solid membrane of the solid-liquid binary system is composed of a polymer containing hydrophilic groups and an alkaline solution, such as the polybenzimidazole-potassium hydroxide solution ion solvent membrane, which combines the high gas barrier properties of dense polymer films and the high conductivity of alkaline solution electrolytes. However, the anion exchange membrane has a high swelling rate after absorbing alkaline solution, resulting in a decrease in its mechanical properties. The usual improvement methods involve the design of new monomers, cross-linking and organic-inorganic composites, and the processes are relatively complicated. Summary of the invention
[0005] Based on this, some embodiments of the present application provide an ion exchange membrane and a preparation method and application thereof. There is no need to design new monomers and prepare the ion exchange membrane through complex reactions such as cross-linking and organic-inorganic composites. An ion exchange membrane with excellent mechanical properties and good conductivity can be obtained. The operation is simple and easy, the cost is low, and the modification effect is obvious.
[0006] In a first aspect, a method for preparing an ion exchange membrane is provided, comprising:
[0007] A first polymer film is provided, wherein the general structural formula of the first polymer film is shown in the following formula (I):
[0008] Formula (I);
[0009] Wherein, R is a C1~C4 alkylene group, Ar is a C6~C 18Arylene or C3~C 10 Divalent heteroaryl
[0010] Deprotonating the first polymer membrane to obtain a second polymer membrane;
[0011] The second polymer membrane is stretched to modify the second polymer membrane and prepare the ion exchange membrane.
[0012] Optionally, the first polymer membrane is subjected to a deprotonation treatment to obtain a second polymer membrane, comprising:
[0013] The first polymer membrane is immersed in a first alkaline aqueous solution for a first preset time to perform a deprotonation treatment on the first polymer membrane.
[0014] Optionally, the preparation method satisfies at least one of the following conditions:
[0015] (1) the alkali used in the first alkaline aqueous solution includes at least one of potassium hydroxide, sodium hydroxide, lithium hydroxide, cesium hydroxide, magnesium hydroxide, calcium hydroxide, potassium carbonate, sodium carbonate, potassium bicarbonate and sodium bicarbonate;
[0016] (2) The concentration of the first alkaline aqueous solution is 5wt%~30wt%;
[0017] (3) The first preset time is 4h~24h.
[0018] Optionally, stretching the second polymer membrane to modify the second polymer membrane to prepare the ion exchange membrane comprises:
[0019] The first end and the second end of the second polymer film are fixed; the second polymer film is a rectangle, the first end and the second end are two opposite ends of the rectangle along a first direction or a second direction, the first direction is an extension direction of a first side of the rectangle, the second direction is an extension direction of a second side of the rectangle, the first direction and the second direction are perpendicular, and there is a first length between the first end and the second end;
[0020] A tensile force is applied to the second end and / or the first end of the second polymer to stretch the second polymer film until the distance between the first end and the second end of the second polymer film is stretched to a second length, wherein the second length is greater than the first length.
[0021] Optionally, the preparation method satisfies at least one of the following conditions:
[0022] (1) The stretching rate is 10 mm / min to 30 mm / min;
[0023] (2) The second length is 2 to 3 times the first length;
[0024] (3) The first length is the length of the first side or the second side of the rectangle minus the length of the first end and the second end in the first direction or the second direction;
[0025] (4) The length of the first end and the second end in the first direction or the second direction is 1 / 5 of the length of the first side or the second side of the rectangle.
[0026] Optionally, after deprotonating the first polymer membrane to obtain a second polymer membrane, and stretching the second polymer membrane to modify the second polymer membrane, before preparing the ion exchange membrane, the preparation method further comprises:
[0027] measuring the electrical conductivity of the second polymer film;
[0028] After modifying the second polymer membrane to prepare the ion exchange membrane, the preparation method further comprises:
[0029] The ion exchange membrane is cut into the same shape as the second polymer membrane, and the conductivity of the ion exchange membrane is measured using the same conductivity measurement method as that of the second polymer membrane.
[0030] In a second aspect, an ion exchange membrane is provided, wherein the ion exchange membrane is prepared by the preparation method described in the first aspect.
[0031] Optionally, the ion exchange membrane satisfies at least one of the following conditions:
[0032] (1) The tensile strength of the ion exchange membrane is 12.4 MPa to 200 MPa;
[0033] (2) The Young's modulus of the ion exchange membrane is 234 MPa to 5437 MPa;
[0034] (3) The conductivity of the ion exchange membrane is 34.5 mS / m to 38.5 mS / m.
[0035] Optionally, the ion exchange membrane has a thickness of 5 μm to 100 μm.
[0036] In a third aspect, there is provided a use of the ion exchange membrane described in the second aspect as an anion exchange membrane or an ion solvent membrane.
[0037] Compared with the related art, this application has the following beneficial effects:
[0038] By deprotonating the first polymer membrane, the alkali corrosion resistance, mechanical properties and anion conductivity of the first polymer membrane can be improved to obtain a second polymer membrane suitable for anion exchange. Then, by stretching the second polymer membrane after the deprotonation treatment, the second polymer membrane can be further modified to optimize the crystallinity, molecular chain arrangement and crystal orientation in the second polymer membrane, thereby improving the mechanical properties of the ion exchange membrane, such as enhancing strength and modulus, and maintaining a high electrical conductivity of the ion exchange membrane, thereby solving the problems in the related art that the ion exchange membrane has a high swelling rate after absorbing alkali solution, resulting in a decrease in its mechanical properties, and that new monomers need to be designed, and the processes of cross-linking and organic-inorganic composites are relatively complicated. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 A schematic flow chart of a method for preparing an ion exchange membrane provided in an embodiment of the present application. DETAILED DESCRIPTION
[0040] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0042] The present application will be further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thoroughly understood.
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0044] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0045] In the present application, reference to a numerical range includes both endpoints of the numerical range unless otherwise specified.
[0046] In this application, when it comes to percentage concentration, unless otherwise specified, it refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.
[0047] In this application, when it comes to temperature parameters, unless otherwise specified, both constant temperature treatment and treatment within a certain temperature range are permitted. The constant temperature treatment allows the temperature to fluctuate within the precision range controlled by the instrument.
[0048] In this application, "arylene" refers to an aromatic hydrocarbon group derived from an aromatic ring compound by removing two hydrogen atoms. It can be a monocyclic aromatic group, a condensed aromatic group, or a polycyclic aromatic group. For polycyclic rings, at least one is an aromatic ring system. For example, "C6~C 12 "Aryl" refers to an aromatic group containing 6 to 12 carbon atoms, each occurrence of which can be independently C6 aromatic, C 10 Aryl, C 14 Aryl or C 18 Suitable examples include, but are not limited to, benzene, biphenyl, naphthalene, anthracene, phenanthrene, perylene, triphenylene, and derivatives thereof.
[0049] "Heteroaryl" means that at least one carbon atom in an aryl group is replaced by a non-carbon atom, such as an N atom, an O atom, or an S atom. For example, "C3~C 10 The term "heteroaryl" refers to a heteroaryl group containing 3 to 10 carbon atoms, which may be independently C3 heteroaryl, C4 heteroaryl, C5 heteroaryl, C6 heteroaryl, C7 heteroaryl or C8 heteroaryl at each occurrence. Suitable examples include, but are not limited to, furan, benzofuran, thiophene, benzothiophene, pyrrole, pyrazole, triazole, imidazole, oxazole, oxadiazole, thiazole, tetrazole, indole, carbazole, pyrroloimidazole, pyrrolopyrrole, thienopyrrole, thienothiophene, furopyrrole, furofuran, thienofuran, benzisoxazole, benzisothiazole, benzimidazole, pyridine, pyrazine, pyridazine, pyrimidine, triazine, quinoline, isoquinoline, o-naphthyridine, quinoxaline, phenanthridine, primary idine, quinazoline and quinazolinone.
[0050] Here, the divalent heteroaryl group refers to a heteroaryl group derived from heteroarene by removing two hydrogen atoms from two carbon atoms.
[0051] In view of the fact that the ion exchange membrane in the related art has a high swelling rate after absorbing alkali solution, resulting in a decrease in mechanical properties, and the common improvement methods involve the design of new monomers of the material, cross-linking and organic-inorganic composites, etc., and the processes are relatively complicated, the specific implementation methods of the present application are described as follows:
[0052] In a first aspect, some embodiments of the present application provide a method for preparing an ion exchange membrane, such as Figure 1 As shown, the preparation method comprises:
[0053] S11), providing a first polymer film; the general structural formula of the first polymer film is shown in the following formula (I):
[0054] Formula (I);
[0055] Wherein, R is a C1~C4 alkylene group, Ar is a C6~C 18 Arylene or C3~C 10 A divalent heteroaryl group; n is 50-2500.
[0056] Wherein, S11), providing a first polymer film may include:
[0057] S111), subjecting an aromatic tetraamine and an aromatic diacid or a derivative thereof to a polycondensation reaction to prepare a polymer;
[0058] S112), casting the polymer to obtain the first polymer film.
[0059] Among them, taking the first polymer film as m-PBI film as an example, the aromatic tetraamine can be 3,3',4,4'-biphenyltetramine (TAB), the aromatic diacid can be 1,3-phthalic acid, and the solvent can be polyphosphoric acid (PPA), which can cause the aromatic tetraamine and the aromatic diacid or its derivatives to undergo a condensation reaction, and the temperature of the condensation reaction is 150~200℃, and the time is 4~24h.
[0060] In some embodiments, in order to improve the polycondensation effect, before the polycondensation reaction occurs, PPA (100 g) can be heated to 120-150° C. under stirring and nitrogen atmosphere, and maintained at 120-150° C. for 30-60 min to remove moisture from polyphosphoric acid (PPA).
[0061] In some embodiments, 3,3',4,4'-biphenyltetramine (TAB) is mechanically stirred at 120°C~150°C for 0.5~4h, then heated to 150~200°C, 1,3-phthalic acid is added to the heated 3,3',4,4'-biphenyltetramine (TAB), and the reaction is carried out for 4~24h to obtain the polymer m-PBI, and the molar ratio of 3,3',4,4'-biphenyltetramine (TAB) to 1,3-phthalic acid can be 0.9:1~1.2:1.
[0062] After the reaction is completed, in order to separate the polymer m-PBI and the acidic solvent, the reaction product can be added to an alkaline solution to wash the acidic solvent, thereby obtaining the polymer m-PBI, wherein the alkaline solution can be, for example, a sodium bicarbonate (NaHCO3) solution. In order to improve the washing effect, the sodium bicarbonate solution can be boiled for washing.
[0063] S112), casting the precursor material to obtain the first polymer film may include:
[0064] preparing a film casting solution of the precursor material;
[0065] The casting solution is cast on a glass plate and dried to remove the solvent to obtain the first polymer film.
[0066] Here, taking the first polymer film as an m-PBI film as an example, the precursor material can be dissolved in DMAc to prepare the casting solution. For example, the precursor material can be dissolved in DMAc by stirring at 60-150° C. Then, the casting solution can be cast on a cooling plate by coating, and dried at 40-100° C. for 8-24 hours to remove the solvent, thereby obtaining the first polymer film.
[0067] S12), deprotonating the first polymer membrane to obtain a second polymer membrane;
[0068] Deprotonation treatment refers to removing hydrogen from the imidazole ring in the first polymer membrane to form more imidazole ring anions. These hydrophilic sites can attract and bind to electrolyte solutions (such as KOH aqueous solutions) to form channels and environments that are conducive to anion transport, thereby preparing an ion exchange membrane for anion exchange, which can facilitate the transmission of anions in the membrane and improve the ion conductivity of the ion exchange membrane.
[0069] This is because: after deprotonation, the polarity of the second polymer membrane changes relative to the first polymer membrane, and the hydrophilicity is enhanced, which will prompt the second polymer membrane to absorb more highly conductive electrolyte solution, ensuring the high ion conductivity of the second polymer membrane. At the same time, the hydrogen bonding effect of the second polymer membrane that absorbs the alkali solution can ensure the mechanical strength and dimensional stability of the second polymer membrane, thereby giving the second polymer better mechanical properties and anion conductivity, and then giving the ion exchange membrane better mechanical properties and anion conductivity.
[0070] In addition, since the hydrogen on the imidazole ring is removed in the deprotonated second polymer membrane, the imidazole ring becomes negatively charged, which increases the attack energy barrier of the hydroxide ion on the imidazole ring, thereby reducing the degradation risk of the subsequently prepared ion exchange membrane under alkaline conditions and improving the alkaline stability of the ion exchange membrane.
[0071] In some embodiments, S12), deprotonating the first polymer membrane to obtain a second polymer membrane comprises:
[0072] The first polymer membrane is immersed in a first alkaline solution for a first preset time to perform a deprotonation treatment on the first polymer membrane.
[0073] In some embodiments, the preparation method satisfies at least one of the following conditions:
[0074] (1) the alkali used in the first alkaline solution includes at least one of potassium hydroxide, sodium hydroxide, lithium hydroxide, cesium hydroxide, magnesium hydroxide, calcium hydroxide, potassium carbonate, sodium carbonate, potassium bicarbonate and sodium bicarbonate;
[0075] (2) The concentration of the first alkaline solution is 5wt%~30wt%;
[0076] (3) The first preset time is 4h~24h.
[0077] In these embodiments, the first polymer membrane may be deprotonated as completely as possible.
[0078] S13), stretching the second polymer membrane to modify the second polymer membrane to prepare an ion exchange membrane.
[0079] In the preparation method of the ion exchange membrane provided in the embodiment of the present application, the alkali corrosion resistance, mechanical properties and anion conductivity of the first polymer membrane can be improved by deprotonating the first polymer membrane, so as to obtain a second polymer membrane suitable for anion exchange. Then, by stretching the second polymer membrane after the deprotonation treatment, the second polymer membrane can be further modified to optimize the crystallinity, molecular chain arrangement and crystal orientation in the second polymer membrane, thereby improving the mechanical properties of the ion exchange membrane, such as enhancing strength and modulus, and maintaining a high electrical conductivity of the ion exchange membrane, thereby solving the problems in the related art that the anion exchange membrane has a high swelling rate after absorbing alkali solution, resulting in a decrease in its mechanical properties, and that new monomers need to be designed, and the processes of cross-linking and organic-inorganic composites are relatively complicated.
[0080] In some embodiments, S13), stretching the second polymer membrane to modify the second polymer membrane to prepare an ion exchange membrane may include:
[0081] The first end and the second end of the second polymer film are fixed; the second polymer film is rectangular, the first end and the second end are two opposite ends of the rectangle along a first direction or a second direction, the first direction is an extension direction of a first side of the rectangle, the second direction is an extension direction of a second side of the rectangle, the first direction and the second direction are perpendicular, and there is a first length between the first end and the second end;
[0082] A tensile force is applied to the first end and / or the second end of the second polymer to stretch the second polymer film until the distance between the first end and the second end of the second polymer film is stretched to a second length, and the second length is greater than the first length.
[0083] In these embodiments, the second polymer film does not break when the distance between the first end and the second end of the second polymer film is stretched to the second length.
[0084] The length of the first side and the length of the second side may be equal or different, which is not specifically limited here. When the length of the first side and the length of the second side are different, the stretching direction of the second polymer film may be the long side extension direction or the short side extension direction.
[0085] In some embodiments, the preparation method satisfies at least one of the following conditions:
[0086] (1) The stretching rate is 10 mm / min ~30 mm / min;
[0087] (2) The second length is 2 to 3 times the first length;
[0088] (3) The first length is the length of the first side or the second side of the rectangle minus the length of the first end and the second end in the first direction or the second direction;
[0089] (4) The length of the first end and the second end in the first direction or the second direction is 1 / 5 of the length of the first side or the second side of the rectangle.
[0090] In these embodiments, when stretched, the stretched length, i.e., the first length, accounts for 3 / 5 of the length of the first side or the second side of the rectangle, and the length clamped by the first end and the second end is 1 / 5 of the length of the first side or the second side of the rectangle.
[0091] In some embodiments, after deprotonating the first polymer membrane to obtain the second polymer membrane, and stretching the second polymer membrane to modify the second polymer membrane, before preparing the ion exchange membrane, the preparation method further includes:
[0092] measuring the electrical conductivity of the second polymer film;
[0093] After modifying the second polymer membrane to prepare the ion exchange membrane, the preparation method further comprises:
[0094] The ion exchange membrane is cut into the same shape as the second polymer membrane, and the conductivity of the ion exchange membrane is measured using the same conductivity measurement method as the second polymer membrane.
[0095] In these embodiments, by measuring the conductivity of the second polymer membrane, and then, after modifying the second polymer membrane to prepare an ion exchange membrane, cutting the ion exchange membrane into the same shape as the second polymer membrane, and measuring the conductivity of the ion exchange membrane using the same conductivity measurement method as the second polymer membrane, the performance of the ion exchange membrane, such as the conductivity, and the performance of the second polymer membrane, such as the conductivity, can be compared, thereby objectively evaluating the modification effect of the ion exchange membrane.
[0096] It should be noted that, in order to prevent the solvent of the stretched ion exchange membrane from volatilizing too quickly and thus drying out, the ion exchange membrane may be immersed in an alkaline solution for a certain period of time before measuring the conductivity of the ion exchange membrane.
[0097] In a second aspect, some embodiments of the present application provide an ion exchange membrane, which is prepared by the preparation method described in the first aspect.
[0098] In some embodiments, the ion exchange membrane satisfies at least one of the following conditions:
[0099] (1) The tensile strength of ion exchange membranes is 12.4 MPa ~200 MPa;
[0100] (2) The Young's modulus of ion exchange membrane is 234 MPa ~5437 MPa;
[0101] (3) The conductivity of the ion exchange membrane is 34.5 mS / m ~38.5 mS / m.
[0102] The tensile strength and Young's modulus can be measured at room temperature (25℃~30℃) using a universal testing machine (ZQ-990L), and the conductivity can be measured using a Gamry electrochemical workstation Reference 3000 impedance analyzer.
[0103] In these embodiments, the ion exchange membrane has excellent mechanical properties and good electrical conductivity, and can improve the mechanical properties of the ion exchange membrane while satisfying the ion conductivity performance, thereby improving the operation stability of the device.
[0104] In some embodiments, the ion exchange membrane has a thickness of 5 μm to 100 μm.
[0105] In these embodiments, the ion exchange membrane is relatively thin. A thinner ion exchange membrane can provide a lower ion transport resistance because the path that ions need to migrate through is shorter, thereby helping to improve ion conductivity.
[0106] In a third aspect, some embodiments of the present application provide a use of the ion exchange membrane described in the second aspect as an anion exchange membrane or an ion solvent membrane.
[0107] The electrolyte used in the electrolysis of water to produce hydrogen can be an alkaline electrolyte, and the ion exchange membrane has excellent mechanical properties and high hydroxide ion conductivity, which can meet the growing demand for the use of ion exchange membranes.
[0108] The above introduces the specific implementation methods of the present application. In order to objectively illustrate the technical effects produced by the present application, the following examples and comparative examples will be used for description.
[0109] In the following examples and comparative examples, all raw materials can be purchased in commercial form, and in order to maintain the reliability of the experiment, the raw materials used in the following examples and comparative examples have the same physical and chemical parameters or are processed in the same way.
[0110] Example 1
[0111] Example 1 provides a method for modifying and testing the performance of an m-PBI membrane, and the specific steps are as follows:
[0112] Step 1), synthesis of m-PBI: PPA (100 g) was heated to 150 ° C and kept in a three-necked flask equipped with mechanical stirring and nitrogen atmosphere (200 mL / min) for 60 min. 3,3',4,4'-Biphenyltetramine (TAB) (0.09 mol) and PPA were added to a three-necked flask, mechanically stirred at 150 ° C for 3 h, and then heated to 200 ° C, 1,3-benzenedicarboxylic acid (0.1 mol) was poured into the three-necked flask and reacted for 24 h. After the polymerization reaction, the resulting polymer was poured into ultrapure water and boiled in a sodium bicarbonate (NaHCO3) solution to separate the m-PBI polymer. In addition, the solution was boiled in ultrapure water to remove impurities. The product was dried for 24 h. m-PBI (4 g) was dissolved in DMAc (40 ml) and stirred vigorously at 100 ° C to prepare an m-PBI casting solution. The m-PBI film solution was coated and cast on a glass plate, and the glass plate was dried in an oven at 60° C. for 24 h. After the solvent evaporated, the obtained m-PBI film was peeled off from the glass plate.
[0113] Step 2) pre-treating the m-PBI membrane: immersing the m-PBI membrane in a 30 wt % KOH aqueous solution for 24 hours, then cutting it into a circle with a diameter of 3.5 cm, and measuring the initial conductivity of the circular sample using an impedance analyzer.
[0114] Step 3), take out the soaked rectangular m-PBI membrane from the KOH aqueous solution and wipe off the excess liquid on the surface, ensure that the opposite ends of the short side of the m-PBI membrane are aligned in the clamp of the tensile testing machine to avoid lateral sliding or twisting during the stretching process, start the tensile testing machine, and stretch the m-PBI membrane at a preset rate of 10 mm / min until the length of the short side of the m-PBI membrane (3 cm) is stretched to twice the previous length (6 cm), then stop the test.
[0115] Step 4), the m-PBI membrane after stretching was cut into a circle with a diameter of 3.5 cm, and the circular sample was immersed in a 30wt% KOH aqueous solution for 24 hours. The conductivity of the m-PBI membrane after stretching was tested using a Gamry electrochemical workstation Reference 3000 impedance analyzer to evaluate the effect of tension treatment on the conductivity of the m-PBI membrane.
[0116] Example 2
[0117] The method for modifying and testing the performance of the m-PBI membrane provided in Example 2 is basically the same as that in Example 1, except that:
[0118] In step 3), the stretching rate is 20 mm / min.
[0119] Example 3
[0120] The method for modifying and testing the performance of the m-PBI membrane provided in Example 3 is basically the same as that in Example 1, except that:
[0121] In step 3), the stretching rate is 30 mm / min.
[0122] Example 4
[0123] The method for modifying and testing the performance of the m-PBI membrane provided in Example 4 is basically the same as that in Example 1, except that:
[0124] In both step 2) and step 4), the m-PBI membrane is immersed in a 5 wt % KOH aqueous solution.
[0125] Example 5
[0126] The method for modifying and testing the performance of the m-PBI membrane provided in Example 5 is substantially the same as that in Example 4, except that:
[0127] In step 3), the stretching rate is 20 mm / min.
[0128] Example 6
[0129] The method for modifying and testing the performance of the m-PBI membrane provided in Example 6 is substantially the same as that in Example 4, except that:
[0130] In step 3), the m-PBI film was stretched until the length of the short side of the m-PBI film (3 cm) was stretched to 2.5 times the previous length (7.5 cm), and the test was stopped.
[0131] Example 7
[0132] The method for modifying and testing the performance of the m-PBI membrane provided in Example 7 is substantially the same as that in Example 6, except that:
[0133] In step 3), the stretching rate is 20 mm / min.
[0134] Example 8
[0135] The method for modifying and testing the performance of the m-PBI membrane provided in Example 8 is substantially the same as that in Example 6, except that:
[0136] In step 3), the stretching rate is 30 mm / min.
[0137] Example 9
[0138] The method for modifying and testing the performance of the m-PBI membrane provided in Example 9 is substantially the same as that in Example 8, except that:
[0139] In step 3), the m-PBI film was stretched until the length of the short side of the m-PBI film (3 cm) was stretched to three times the previous length (9 cm), and the test was stopped.
[0140] Example 10
[0141] The method for modifying and testing the performance of the m-PBI membrane provided in Example 10 is substantially the same as that in Example 8, except that:
[0142] In both step 2) and step 4), the m-PBI membrane is immersed in a 5 wt % KOH aqueous solution.
[0143] Embodiment 11
[0144] The method for modifying and testing the performance of the m-PBI membrane provided in Example 11 is substantially the same as that in Example 6, except that:
[0145] In step 3), the m-PBI film is stretched until the m-PBI film breaks, and the test is stopped.
[0146] Comparative Example 1
[0147] In Comparative Example 1, the m-PBI membrane is not stretched. After the m-PBI membrane is prepared in step 1), the m-PBI membrane is pretreated, and the conductivity of the pretreated m-PBI membrane is directly tested. The testing method is the same as that of Example 1.
[0148] Test Case
[0149] 1. The conductivity test results of the m-PBI film after stretching measured by an impedance analyzer provided in Examples 1 to 11 and Comparative Example 1 are shown in Table 1 below:
[0150] Table 1
[0151]
[0152] It can be seen from Table 1 that the conductivity of the m-PBI membrane can still be maintained above 35.3 mS / m after stretching, which will not have a significant impact on the ion conductivity of the ion exchange membrane.
[0153] 2. The tensile strength and Young's modulus of the stretched m-PBI films provided in Examples 1 to 11 and the m-PBI film provided in Comparative Example 1 were measured by the following method:
[0154] The stretched m-PBI films provided in Examples 1 to 11 and the m-PBI film provided in Comparative Example 1 were measured at a preset stretching rate on a ZQ universal testing machine (ZQ-990L) at room temperature. Five identical samples were tested for each film, and the average value was taken to obtain the test results of tensile strength and Young's modulus as shown in Table 2 below.
[0155] Table 2
[0156]
[0157] It can be seen from Table 2 that the tensile strength and Young's modulus of the m-PBI film after stretching are greatly improved, especially when the concentration of the KOH aqueous solution is 5wt%, the tensile strength can reach more than 100Mpa, and the Young's modulus can reach more than 4800Mpa. When the concentration of the KOH aqueous solution is constant, as the stretching rate and the stretching ratio increase, the tensile strength and Young's modulus of the m-PBI film after stretching tend to increase. When no stretching is used for modification, such as Comparative Example 1, the tensile strength and Young's modulus of the m-PBI film are small, and the mechanical strength is poor. If the m-PBI film breaks during the stretching process, such as Example 11, its tensile strength and Young's modulus are not much different from those when no stretching is performed.
[0158] In summary, the ion exchange membrane of the present application embodiment has at least the following advantages through the tension treatment method:
[0159] By optimizing the molecular chain arrangement through physical means, tension treatment can quickly improve the mechanical properties of ion exchange membranes, such as enhancing strength and modulus, promoting crystallization, optimizing crystal orientation, and reducing internal defects of the material. While maintaining an effective charge conduction path, it is harmless to the environment, easy to operate, low cost, and does not introduce harmful chemicals, meeting green production requirements.
[0160] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0161] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A method for preparing an ion exchange membrane, characterized in that: include: A first polymer film is provided; the general structural formula of the first polymer film is shown in the following formula (I): Formula (I); Wherein, R is a C1~C4 alkylene group, Ar is a C6~C 18 Arylene or C3~C 10 A divalent heteroaryl group; Deprotonating the first polymer membrane to obtain a second polymer membrane; The second polymer membrane is stretched to modify the second polymer membrane and prepare the ion exchange membrane.
2. The method for preparing an ion exchange membrane according to claim 1, characterized in that: The first polymer membrane is subjected to a deprotonation treatment to obtain a second polymer membrane, comprising: The first polymer membrane is immersed in a first alkaline solution for a first preset time to perform a deprotonation treatment on the first polymer membrane.
3. The method for preparing an ion exchange membrane according to claim 2, characterized in that: The preparation method satisfies at least one of the following conditions: (1) The alkali used in the first alkaline solution includes at least one of potassium hydroxide, sodium hydroxide, lithium hydroxide, cesium hydroxide, magnesium hydroxide, calcium hydroxide, potassium carbonate, sodium carbonate, potassium bicarbonate and sodium bicarbonate; (2) The concentration of the first alkaline solution is 5wt%~30wt%; (3) The first preset time is 4h~24h.
4. The method for preparing an ion exchange membrane according to any one of claims 1 to 3, characterized in that: Stretching the second polymer membrane to modify the second polymer membrane to prepare the ion exchange membrane, comprising: The first end and the second end of the second polymer film are fixed; the second polymer film is a rectangle, the first end and the second end are two opposite ends of the rectangle along a first direction or a second direction, the first direction is an extension direction of a first side of the rectangle, the second direction is an extension direction of a second side of the rectangle, the first direction and the second direction are perpendicular, and there is a first length between the first end and the second end; A tensile force is applied to the second end and / or the first end of the second polymer to stretch the second polymer film until the distance between the first end and the second end of the second polymer film is stretched to a second length, wherein the second length is greater than the first length.
5. The method for preparing the ion exchange membrane according to claim 4, characterized in that: The preparation method satisfies at least one of the following conditions: (1) The stretching rate is 10 mm / min to 30 mm / min; (2) The second length is 2 to 3 times the first length; (3) The first length is the length of the first side or the second side of the rectangle minus the length of the first end and the second end in the first direction or the second direction; (4) The length of the first end and the second end in the first direction or the second direction is 1 / 5 of the length of the first side or the second side of the rectangle.
6. The method for preparing an ion exchange membrane according to any one of claims 1 to 3, characterized in that: After deprotonating the first polymer membrane to obtain a second polymer membrane, and stretching the second polymer membrane to modify the second polymer membrane, before preparing the ion exchange membrane, the preparation method further includes: measuring the electrical conductivity of the second polymer film; After modifying the second polymer membrane to prepare the ion exchange membrane, the preparation method further comprises: The ion exchange membrane is cut into the same shape as the second polymer membrane, and the conductivity of the ion exchange membrane is measured using the same conductivity measurement method as that of the second polymer membrane.
7. An ion exchange membrane, characterized in that: The ion exchange membrane is prepared by the preparation method according to any one of claims 1 to 6.
8. The ion exchange membrane according to claim 7, characterized in that The ion exchange membrane satisfies at least one of the following conditions: (1) The tensile strength of the ion exchange membrane is 12.4 MPa to 200 MPa; (2) The Young's modulus of the ion exchange membrane is 234 MPa to 5437 MPa; (3) The conductivity of the ion exchange membrane is 34.5 mS / m to 38.5 mS / m.
9. The ion exchange membrane according to claim 7 or 8, characterized in that The thickness of the ion exchange membrane is 5 μm to 100 μm.
10. Use of the ion exchange membrane according to any one of claims 7 to 9 as an anion exchange membrane or an ion solvent membrane.
Citation Information
Patent Citations
Naphthalene ring-containing polybenzimidazole proton exchange membrane as well as preparation method and application thereof
CN110993998A
Polyarylene ion exchange membrane and preparation method thereof
CN117866264A
Comb-shaped structure polybenzimidazole anion exchange membrane with high conductivity and preparation method thereof
US20210202972A1